Des-ordenamento territorial e unidades de conservação - Altair Sancho Pivoto dos Santos (2016)
view / environmental protection order. At the same time, the latest theoretical debates on the Planning also point to new possibilities for reflection and debate. First, because They draw attention to the set of economic forces, political and symbolic cultural --- which combine, in different ways, in protected territories. Second, it challenges us to discuss limits and consolidation possibilities for Planning bias more democratic and aligned to this multiplicity of demands simultaneous coexisting in the territories turned into units conservation, this perspective that seeks to minimize the excessive weight of the abstract look in planning exercises conducted by the state. As a result, the practice of planning gains in density and complexity, requiring the efforts of units conservation increased ability to "administration des - sordem", recognizing the full potential of transformation inherent in the process. Inspired by these ideas is that we set out to understand the biases and characteristics of spatial planning processes associated with the Serra do Cipó National Park and Protected Area Environmental Morro da Pedreira, with a close look at the process history of creating these protected areas for the operation of its management councils and the process completion of the management plan for the APA Morro da Pedreira. this effort research, primarily qualitative, it was oriented three major research resources, depending on the situation experienced and their types of involvement in the field: participant observation, interviews and pesquisa-- action The results indicate that the consolidations democratic and integrated Spatial associated the PARNASC and APAMP passes , fundamentally , a changedepth values governing the structure of power and the set rules that underlie the functioning of the councils and other planning practices within the protected areas . It - is therefore a slow and continuous learning which requires real commitment from all involved , in particular ,the managers of protected areas with the adoption of practicesterritorial governance , anchored on effective decentralizationpower , social mobilization and engagement and sharingresponsibilities in the development , implementation and evaluation of policies, programs and projects aimed at conservation and environmental development promotion in the Serra do liana .